Ectopic lipid deposition and insulin resistance in patients with GH disorders before and after treatment - Arlien-Søborg, Mai C; Madsen, Michael Alle; Dal, Jakob; Krusenstjerna-Hafstrøm, Thomas; Ringgaard, Steffen; Skou, Nickolaj; Høgild, Morten; Jørgensen, Jens Otto Lunde (European journal of endocrinology, 2023)
Insulin resistance is associated with ectopic lipid deposition. Growth hormone (GH) status also modulates ectopic lipid accumulation, but how this associates with insulin resistance in patients with GH disorders is not well established. Twenty-one patients diagnosed with acromegaly and 12 patients with adult GH deficiency (GHD) were studied at diagnosis and after treatment. A reference group of 12 subjects was included. Each study day comprised assessment of body composition with dual-energy X-ray absorptiometry, ectopic lipid deposition in the liver by MR spectroscopy, and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR). Disease control of acromegaly decreased lean body mass (LBM) (P < .000) and increased the percentage of total body fat (TBF) (P < .000). GH replacement increased LBM in the GHD patients (P = .007) and decreased the percentage of TBF (P = .010). The intrahepatic lipid (IHL) content increased after disease control in acromegaly (P = .004), whereas IHL did not change significantly after GH replacement in GHD (P = .34). Insulin resistance (HOMA-IR) improved after disease control of acromegaly (P < .000) and remained unaltered after GH replacement in the GHD patients (P = .829). GH status is a significant modulator of body composition and insulin sensitivity.GH excess reduces total fat mass and intrahepatic lipid content together with induction of insulin resistance.The data support the notion that GH-induced insulin resistance is unassociated with hepatic lipid accumulation.